Quality Assessment of OClO Observations by the Odin Satellite - Shooshtari, Pooneh (2011)
Since the discovery of the Antarctic ozone hole by Farman (1985), several research have been done to investigate the scientific reasons of this dramatic phenomenon. Monitoring Chlorine dioxide (OClO) as an indicator of stratospheric chlorine activation is essential to address still open questions regarding the stratospheric halogen chemistry and also ozone depletion. In this study the vertical profiles of stratospheric OClO limb-scattered measurements by the OSIRIS (Optical Spectrograph and InfraRed Imager System) instrument on board the Odin satellite are presented in the austral and boreal winter from 2002 to 2009. A climatology of OSIRIS OClO is constructed in parallel with a ClO climatology from SMR (Sub-Millimetre Radiometer) data for the purpose of comparison. A year to year variation of OClO daily mean is studied and compared to the ClO concentrations. The results and the relation between the two species are in consistent with the general understanding of stratospheric chlorine chemistry. Furthermore, the relationship between ClO and OClO is analyzed. Though, the OClO measurements are detected at the right time and place, very limited amount of data and also strong influence of SZA on the measurements (i.e. significant diurnal variation) make it difficult to analyze the results. To evaluate the quality of OClO measurements, the OSIRIS OClO data is compared to the coincident OClO measurements by the SCIAMACHY instrument onboard the ENVISAT on 15th and 16th of September 2008. Because of too few coincidences, no statistical analysis can be provided. Validation to SCIAMACHY shows large systematic differences between 12 to 20 km. The OSIRIS OClO profiles are also compared to the SLIMCAT simulations. Though SLIMCAT underestimates the OClO concentrations at SZAs> 92°, the shape of the OSIRIS OClO profiles look reasonable compare to the simulated data. Validerat; 20110324 (anonymous)